Negative OC photoresist with low residual stress and high refractive index as well as preparation method and application of photocuring pattern

By using materials such as high refractive index nanoparticles and epoxy monomers in high refractive index photoresist formula, the internal stress is adjusted, and the problem of high residual stress of photoresist is solved, which improves the mechanical strength and storage stability of photoresist , suitable for high-precision applications such as OLED panels.

CN119126490APending Publication Date: 2024-12-13XIAN SMART MATERIALS CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411384731.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing high refractive index photoresist has high residual stress, which leads to reduced material conductivity, weakened corrosion resistance and undercut problems of OLED panel packaging structure, affecting equipment performance.

Method used

Using a high refractive index negative OC photoresist formula with low residual stress, including high refractive index nanoparticles, epoxy monomers, acrylic resins and acrylic monomers, modulation of internal stress and polymerization through specific mass ratios and ligand modifications , increase the rigidity and dispersion of the photoresist and reduce residual stress.

Benefits of technology

Effectively reduce the residual stress of photoresist, improve the mechanical strength and storage stability of photoresist, avoid warping and deformation, enhance the accuracy and integrity of photocuring patterns, and is suitable for applications such as microlens arrays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005070740670000031
    Figure BDA0005070740670000031
  • Figure BDA0005070740670000161
    Figure BDA0005070740670000161
  • Figure BDA0005070740670000181
    Figure BDA0005070740670000181
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and relates to a negative OC photoresist with low residual stress and high refractive index as well as a preparation method and application of the negative OC photoresist. The negative photoresist with the high refractive index at least comprises the following raw materials in parts by weight: 10-22 parts of nanoparticles with the high refractive index, 2-3 parts of an epoxy monomer, 3-10 parts of acrylic resin, 1-3 parts of an acrylic monomer, 1.5-4 parts of a photoinitiator, 0-4 parts of a photosensitizer, 0.01-0.5 part of a surfactant, 0-2 parts of a curing agent and 30-70 parts of a solvent. According to the invention, the epoxy monomer (spiro orthocarbonate compound) is added in the formula to form stable interaction with the nanoparticles, so that the dispersity of the nanoparticles in a polymer matrix is improved, and the overall performance of the photoresist is optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and relates to a preparation method and application of a high-refractive-index negative OC photoresist with low residual stress and a photocurable pattern. Background Art

[0002] Photoresist is often used as a protective layer in panel materials such as liquid crystal displays, LCDs, and monitors. It usually has the characteristics of high transparency, high insulation, and high resolution. In the field of organic light-emitting diodes (OLED), there are currently two main solutions to improve the brightness of OLED panels: Samsung adopts an enhanced bottom-layer driving solution, and LG adopts micro lens arrays (MLA) technology. After LG launched the OLED panel using META technology, Panasonic, Philips, and LG itself all adopted this new panel. The core of the new panel is MLA technology, which is essentially to further reduce brightness loss so that the microlenses can emit as little light as possible when the light is reflected back to the outside and lost. Given the large number of microlenses, even a small amount of light, the overall effect of many microlenses is very significant. However, the presence of residual stress will affect the conductivity of the material, reduce the corrosion resistance of the material, and cause cracks or fractures in the parts. Existing high-refractive index photoresists have high residual stress, which is prone to undercut problems during patterning, destroying the packaging structure of the OLED panel.

[0003] To solve the above problems, a Chinese patent document (publication number: CN117369213A, publication date: January 9, 2024) discloses a flexible high-refractive index negative photoresist. The epoxy photocurable monomers used in the photoresist include epoxy cyclohexane or epoxy cyclobutane photocurable cationic monomers, which can only reduce the residual stress of the system to a certain extent, and cannot be reduced to the ideal level. In addition, its passing rate of the subsequent double 85 test is low, and the device performance will also be affected.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a method for preparing a negative OC photoresist with a high refractive index and a photocurable pattern with low residual stress and application. The purpose of the present invention is achieved through the following technical solutions:

[0006] In the first aspect, the present invention provides a high-refractive index negative OC photoresist with low residual stress, which includes the following raw materials in parts by weight: 10 to 22 parts of high-refractive index nanoparticles, 2 to 3 parts of epoxy monomers, 3 to 10 parts of acrylic resins, 1 to 3 parts of acrylic monomers, 1.5 to 4 parts of photoinitiators, 0 to 4 parts of photosensitizers, 0.01 to 0.5 parts of surfactants, 0 to 2 parts of curing agents, and 30 to 70 parts of solvents.

[0007] Specifically, the high refractive index nanoparticles are selected from one or two of ZrO2, TiO2, In2O3, Al2O3, ZnO, and SnO2; preferably, the high refractive index nanoparticles are 6 to 15 parts.

[0008] Furthermore, the average particle size of the high refractive index nanoparticles is 5 to 22 nm, and the refractive index is 1.8 to 2.0. The high refractive index nanoparticles in the present invention are modified with ligands, and acrylate ligands are connected to the surface, and are purchased from JSR, Nippon Shokubai and other companies. On the one hand, the high refractive index nanoparticles can increase the refractive index of the photoresist, change the size and distribution of internal stress, increase the rigidity of the photoresist, and help resist deformation caused by internal stress; at the same time, it can also affect the process and mechanism of polymerization or curing reaction, thereby indirectly regulating internal stress. On the other hand, the high refractive index nanoparticles will have a strong induced polarization effect on the surrounding hybrids, resulting in a significant change in dissolution behavior, thereby achieving a high-sensitivity and high-resolution lithography effect.

[0009] Specifically, the epoxy monomer is selected from spirocyclic orthocarbonate compounds, which are used to improve the volume stability of the material and reduce the stress during the polymerization process, and its structural formula is one of the following structural formulas:

[0010]

[0011] Furthermore, the mass ratio of the high refractive index nanoparticles to the epoxy monomer is (3-11):1. The inventors of the present application have found through research that the high refractive index nanoparticles are prone to aggregation due to their hydrophilicity and high surface energy. As the content of the nanophase increases, the transparency of the material decreases rapidly. Moreover, only when the mass ratio of the high refractive index nanoparticles to the epoxy monomer is within the range of (3-11):1, preferably the mass ratio of the high refractive index nanoparticles to the epoxy monomer is within the range of (5-8):1, the introduction of spiro orthocarbonate can not only offset the volume shrinkage of the photoresist caused by the change in the intermolecular distance (i.e., from the van der Waals distance to the covalent bond distance) during the curing process, but also improve the dispersibility of the high refractive index nanoparticles in the photoresist. This is because the spiro orthocarbonate can act on the surface of the nanoparticles through its polar functional group, thereby increasing the affinity between the nanoparticles and the photoresist and reducing the agglomeration phenomenon.

[0012] Specifically, the acrylic resin is a UV-curable acrylic oligomer, including Lisenoco polymer material BSR-2, BSR-3 (viscosity of 30-300 cps at 25° C.), Changxing UV resin ETERCURE 6148J-75 or TTT Corporation's TT6900.

[0013] Specifically, the acrylic monomer is a mixture of one or more of the following: monofunctional (meth)acrylate of C1 to C30 monohydric alcohol or polyhydric alcohol, difunctional (meth)acrylate of C2 to C30 monohydric alcohol or polyhydric alcohol, and multifunctional (meth)acrylate of C3 to C30 monohydric alcohol or polyhydric alcohol.

[0014] Among them: acrylic acid monomer has multiple reactive sites, can form a more complex cross-linked network structure, stabilize inorganic particles, avoid high refractive index nanoparticles agglomeration, do not affect the resolution while making the photocured pattern on the silicon nitride substrate better adhesion and storage stability; at the same time, can increase the mechanical strength and stability of the photoresist, help to disperse and withstand internal stress, reduce the defects caused by internal stress concentration; and its higher cross-linking density may also have a certain inhibitory effect on shrinkage stress. The viscosity and mass ratio of the monofunctional (meth) acrylate, difunctional (meth) acrylate and multifunctional (meth) acrylate in the present invention are within a specific range, can achieve the delay of the time of the gel point, shrinkage stress will also be reduced accordingly, and at the same time can improve the curing rate, enhance the ability of the photoresist cured film to resist temperature and humidity (85°C, 85%), and improve storage stability.

[0015] Furthermore, the mass ratio of monofunctional (meth)acrylate, difunctional (meth)acrylate and multifunctional (meth)acrylate is 1:(2-3):(2-4). Adding acrylic monomers within this numerical range can effectively solve the problem of excessive residual stress of the photoresist after curing.

[0016] Among them: the monofunctional acrylate monomer can be selected from any one of lauric acid acrylate, isodecyl acrylate, isooctyl acrylate, isononyl acrylate, isodecyl methacrylate, lauric acid methacrylate and ethoxyethoxyethyl acrylate. Such monofunctional acrylate monomers have the characteristics of good flexibility, water solubility, low shrinkage, etc. As the flexible chains in the monofunctional acrylate monomers continue to increase, the flexibility of the cured material will increase significantly. It is precisely because of this enhanced flexibility that the shrinkage stress is reduced. During curing, the monomers are transformed into network macromolecules, which will produce volume shrinkage and shrinkage stress. Under the premise of ensuring that the high refractive index nanoparticles do not agglomerate, the flexibility of the film after the formula is cured can be effectively improved.

[0017] The viscosity of the bifunctional acrylate monomer at room temperature is 80 to 1500 cps. Any one of tricyclodecane dimethanol diacrylate (viscosity 110 to 150 cps), ethoxylated bisphenol A diacrylate BPA10EODA (viscosity 350 to 800 cps), ethoxylated bisphenol A dimethacrylate BPA2EODMA (viscosity 900 to 1300 cps), and tricyclodecane dimethanol dimethacrylate (viscosity 80 to 120 cps) can be selected. The bifunctional acrylate monomer is flexible and has a balance between hydrophobicity and hydrophilicity.

[0018] The multifunctional acrylate monomer has the characteristics of high crosslinking density and fast curing, and has a viscosity of 70 to 1000 cps at room temperature; preferably, the viscosity is 80 to 900 cps, including pentaerythritol triacrylate (viscosity 400 to 550 cps), ethoxylated trimethylolpropane trimethacrylate (viscosity 80 to 110 cps), pentaerythritol tetraacrylate (viscosity 400 to 650 cps), ethoxylated pentaerythritol tetraacrylate (viscosity 120 to 170 cps), ditrimethylolpropane tetraacrylate (viscosity 400 to 700 cps), and propoxylated pentaerythritol tetraacrylate (viscosity 180 to 240 cps).

[0019] Specifically, the photoinitiator includes an oxime ester photoinitiator and a cationic photoinitiator, and the oxime ester photoinitiator includes one or more of OXE-01, OXE-02, OXE-E12, and OXPI-405; wherein OXE-01 is 1-(4-phenylthiophenyl)-octane-1,2-dione-2-benzoic acid oxime ester (CAS No.: 253585-83-0), and OXE-02 is 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(O-acetyl oxime) (CAS No.: 478556-66-0). The cationic photoinitiator includes one or more of diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate, bis(4-tert-butylphenyl)iodonium hexafluorophosphate, triphenylsulfonium hexafluorophosphate, and triphenyltetrakis(pentafluorophenyl)boratesulfonium.

[0020] The amount of the cationic photoinitiator added is 2-4% of the amount of the epoxy monomer added. The light absorption of the combination of the oxime ester photoinitiator and the cationic photoinitiator in the exposure band and the total band can effectively reduce the line width growth generated in the subsequent preparation of the photoresist, and improve the curing rate of the acrylic prepolymer and the monomer in the photoresist composition during exposure.

[0021] Specifically, the photosensitizer includes one or more of 2-isopropylthioxanthone, 9,10-dibutoxyanthracene, benzoin dimethyl ether, 1-hydroxycyclohexyl phenyl ketone, 1-chloro-4-propoxythioxanthone, and ethyl p-N,N-dimethylaminobenzoate.

[0022] Specifically, the curing agent includes one or more of methyltetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylnadic anhydride, acetic anhydride, propionic anhydride, benzyldimethylamine, N,N-dimethylcyclohexylamine, bis(2-dimethylaminoethyl) ether, N,N,N',N'-tetramethylalkylenediamine, and triethylamine.

[0023] It should be noted that the addition amount of the photosensitizer and the curing agent in the present invention can be 0, and the photoresist can be cured at a wavelength of 365nm; when the photosensitizer and the curing agent are added, the photoresist can be cured at a wavelength of 395nm.

[0024] Specifically, the surfactant includes F-114, F-553, F-562 or F-570 manufactured by DIC, FC-135 or FC-170C manufactured by 3M, S-211, S-221, S-231 or S-242 manufactured by AGC, BYK-300, BYK-301, BYK-302, BYK-306, BYK-310, BYK-313, BYK-320, BYK-366P, BYK-368P, BYK-370, BYK-375, BYK-377, BYK-378, or BYK-394 manufactured by BYK. The above surfactants help to reduce the surface tension and surface tension gradient of the coating, thereby improving the wettability and adhesion of the coating on the substrate. In addition, it can also promote the rapid flow of the coating before it solidifies into a film, eliminating or reducing defects such as orange peel, brush marks, ripples, shrinkage holes, etc., making the film formation more uniform and natural.

[0025] Specifically, the solvent is an alcohol such as 3-methoxy-1-butanol and diacetone alcohol; or, the solvent is a ketone such as acetone, methyl ethyl ketone, cyclohexanone, N-methyl-2-pyrrolidone; or, the solvent is an aromatic hydrocarbon such as toluene, xylene, tetramethylbenzene; or, the solvent is a glycol ether such as diethylene glycol ethyl methyl ether, propylene glycol methyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether; or, the solvent is ethyl acetate, butyl acetate, ethyl lactate, 3-methoxybutyl acetate, 3-methoxy-3-butyl acetate or propylene glycol methyl ether acetate.

[0026] In a second aspect, the present invention further provides a photocurable pattern formed by the above-mentioned low residual stress high refractive index negative photoresist, which can be used for, but not limited to, microlens arrays, array flattening film patterns, protective film patterns, insulating film patterns, etc. It should be emphasized that the photocurable pattern provided by the present invention is particularly suitable for microlens arrays.

[0027] Specifically, the photocurable pattern is prepared by coating the high refractive index negative photoresist with low residual stress on the substrate, and then preparing the photocurable pattern by exposure and development. The specific preparation method is as follows:

[0028] 1) first coating the above-mentioned low residual stress high refractive index negative photoresist on a substrate; wherein the coating method adopts other coating methods such as spin coating, casting, roller coating, slit coating, etc., preferably slit coating;

[0029] 2) After coating, the film is heated and dried to remove volatile components to obtain a smooth film; wherein the heating temperature is 70 to 90° C., and the thickness of the film after heating is usually 2 to 8 μm, preferably 2 to 4 μm;

[0030] 3) The obtained adhesive film is then irradiated with ultraviolet light through a mask, so that the adhesive film cured by ultraviolet light is brought into contact with a developer to dissolve the unexposed area for development. After development, the pattern is washed with water, dried with nitrogen, and then post-baked at a temperature of 70 to 100° C. for 10 to 100 minutes to obtain the desired photocured pattern.

[0031] Finally, the present invention also provides an image display device including the above-mentioned photocuring pattern, which includes a liquid crystal display device, an organic light emitting diode, a flexible display, etc., but is not limited thereto, and can also include all known image display devices that can be applied to the present technical field.

[0032] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:

[0033] 1. The present invention can form stable interaction with nanoparticles by adding epoxy monomer (spiro orthocarbonate compounds) in prescription, so as to improve the dispersibility of nanoparticles in polymer matrix, thereby optimize the overall performance of photoresist. In addition, spiro orthocarbonate compounds provide flexible segments in polymer network with cation initiated polymerization, and volume expansion can occur in polymerization or curing process, and this volume expansion can offset or partially offset the internal stress produced by photoresist curing shrinkage, thereby reduce overall internal stress level and volume shrinkage, improve adhesion and help to reduce deformation and cracking of photoresist film, avoid problems such as warpage deformation in goods, and then improve precision and integrity of photoresist pattern. And, add epoxy monomer, can also improve the flexibility of photoresist cured film, increase the cross-linking density of photoresist film, thereby reduce its residual stress.

[0034] 2. The present invention adjusts the weight proportions of the raw materials, and under a specific weight ratio, the mass ratio of high refractive index nanoparticles to epoxy monomer is (3-11):1, and the mass ratio of monofunctional (meth)acrylate, difunctional (meth)acrylate and multifunctional (meth)acrylate is 1:(2-3):(4-5), which can delay the time of gel point appearance, not only reduce residual stress, but also enhance the ability of photoresist cured film to resist temperature and humidity (85°C, 85%), so that the prepared photoresist has excellent storage stability, improves the refractive index, transmittance and photocuring rate of the photocuring pattern, and avoids the problem of undercutting during patterning. In addition, the present invention provides low cost, stable performance, simple preparation method, strong operability, good repeatability, and has broad application prospects. DETAILED DESCRIPTION

[0035] Here, exemplary embodiments will be described in detail, and the embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are only examples consistent with some aspects of the present invention described in detail in the appended claims.

[0036] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with embodiments.

[0037] Example 1

[0038] This embodiment provides a low residual stress high refractive index negative photoresist (I), which includes the following raw materials in parts by weight:

[0039] 10 parts of high refractive index nanoparticles, 2 parts of epoxy monomer, 3 parts of acrylic resin, 3 parts of acrylic monomer, 1.5 parts of photoinitiator, 2 parts of photosensitizer, 0.1 parts of surfactant, 0.1 parts of curing agent, 60 parts of solvent; wherein:

[0040] The high refractive index nanoparticles are ZrO2 with an average particle size of 5 nm and a refractive index of 1.8;

[0041] The mass ratio of high refractive index nanoparticles to epoxy monomer is 5:1;

[0042] The epoxy monomer is a monomer of formula (1);

[0043] The acrylic resin uses Lisennoco polymer material BSR-2;

[0044] The mass ratio of monofunctional (meth)acrylate, difunctional (meth)acrylate and multifunctional (meth)acrylate in the acrylic monomer is 1:2:4;

[0045] The monofunctional (meth)acrylate is lauric acid acrylate;

[0046] The difunctional (meth)acrylate is tricyclodecane dimethanol diacrylate;

[0047] The multifunctional (meth)acrylate is pentaerythritol triacrylate;

[0048] The photoinitiators used were OXE-01 and diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate (the amount added was 2% of the amount added of the epoxy monomer, the amount added here refers to the added mass, the same below);

[0049] The photosensitizer is 2-isopropylthioxanthone;

[0050] Methyltetrahydrophthalic anhydride is selected as the curing accelerator;

[0051] The surfactant used is BYK-310 from BYK Chemical;

[0052] The solvent is 3-methoxy-1-butanol.

[0053] Example 2

[0054] This embodiment provides a low residual stress high refractive index negative photoresist (II), which includes the following raw materials in parts by weight:

[0055] 15 parts of high refractive index nanoparticles, 2 parts of epoxy monomer, 5 parts of acrylic resin, 3 parts of acrylic monomer, 1.5 parts of photoinitiator, 3 parts of photosensitizer, 0.2 parts of surfactant, 0.5 parts of curing agent, 65 parts of solvent; wherein:

[0056] The high refractive index nanoparticles are ZrO2 with an average particle size of 12 nm and a refractive index of 1.8;

[0057] The mass ratio of high refractive index nanoparticles to epoxy monomer is 7.5:1;

[0058] The epoxy monomer is a monomer of formula (2);

[0059] The acrylic resin uses Lisennoco polymer material BSR-2;

[0060] The mass ratio of monofunctional (meth)acrylate, difunctional (meth)acrylate and multifunctional (meth)acrylate in the acrylic monomer is 1:2:2;

[0061] The monofunctional (meth)acrylate is lauric acid acrylate;

[0062] The difunctional (meth)acrylate is tricyclodecane dimethanol diacrylate;

[0063] The multifunctional (meth)acrylate is pentaerythritol triacrylate;

[0064] The photoinitiators used were OXE-01 and diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate (the amount added was 2% of the amount of epoxy monomer added);

[0065] The photosensitizer is 2-isopropylthioxanthone;

[0066] Acetic anhydride is selected as the curing accelerator;

[0067] The surfactant used is BYK-377 from BYK Chemical;

[0068] The solvent is 3-methoxy-1-butanol.

[0069] Example 3

[0070] This embodiment provides a low residual stress high refractive index negative photoresist (III), which includes the following raw materials in parts by weight:

[0071] 15 parts of high refractive index nanoparticles, 2 parts of epoxy monomer, 8 parts of acrylic resin, 3 parts of acrylic monomer, 1 part of photoinitiator, 2 parts of photosensitizer, 0.3 parts of surfactant, 0.1 parts of curing agent, 70 parts of solvent; wherein:

[0072] The high refractive index nanoparticles are ZrO2 with an average particle size of 10 nm and a refractive index of 1.8;

[0073] The mass ratio of high refractive index nanoparticles to epoxy monomer is 7.5:1;

[0074] The epoxy monomer is a monomer of formula (3);

[0075] The acrylic resin uses Lisennoco polymer material BSR-3;

[0076] The mass ratio of monofunctional (meth)acrylate, difunctional (meth)acrylate and multifunctional (meth)acrylate in the acrylic monomer is 1:2:2;

[0077] The monofunctional (meth)acrylate is selected from isononyl acrylate;

[0078] The difunctional (meth) acrylate is ethoxylated bisphenol A diacrylate BPA10EODA;

[0079] The multifunctional (meth)acrylate is pentaerythritol tetraacrylate;

[0080] The photoinitiators used were OXE-02 and bis(4-tert-butylphenyl)iodonium hexafluorophosphate (the amount added was 3% of the amount of epoxy monomer added);

[0081] The photosensitizer used was 9,10-dibutoxyanthracene;

[0082] Methyltetrahydrophthalic anhydride is selected as the curing accelerator;

[0083] The surfactant used is BYK-306 from BYK Chemical;

[0084] The solvent is 3-methoxy-1-butanol.

[0085] Example 4

[0086] This embodiment provides a low residual stress high refractive index negative photoresist (IV), which includes the following raw materials in parts by weight:

[0087] 20 parts of high refractive index nanoparticles, 3 parts of epoxy monomer, 6 parts of acrylic resin, 3 parts of acrylic monomer, 1 part of photoinitiator, 2 parts of photosensitizer, 0.1 parts of surfactant, 0.1 parts of curing agent, 55 parts of solvent; wherein:

[0088] The high refractive index nanoparticles are ZrO2 with an average particle size of 20 nm and a refractive index of 1.9;

[0089] The mass ratio of high refractive index nanoparticles to epoxy monomer is 20:3;

[0090] The epoxy monomer is a monomer of formula (4);

[0091] The acrylic resin uses Lisennoco polymer material BSR-3;

[0092] The mass ratio of monofunctional (meth)acrylate, difunctional (meth)acrylate and multifunctional (meth)acrylate in the acrylic monomer is 1:3:2;

[0093] The monofunctional (meth)acrylate is ethoxyethoxyethyl acrylate;

[0094] The difunctional (meth) acrylate is ethoxylated bisphenol A diacrylate BPA10EODA;

[0095] The multifunctional (meth)acrylate is pentaerythritol tetraacrylate;

[0096] The photoinitiators used were OXE-02 and bis(4-tert-butylphenyl)iodonium hexafluorophosphate (the amount added was 3% of the amount of epoxy monomer added);

[0097] The photosensitizer used was 9,10-dibutoxyanthracene;

[0098] Acetic anhydride is selected as the curing accelerator;

[0099] The surfactant used is BYK-302 from BYK Chemical;

[0100] The solvent is 3-methoxy-1-butanol.

[0101] Example 5

[0102] This embodiment provides a low residual stress high refractive index negative photoresist (V), which includes the following raw materials in parts by weight:

[0103] 22 parts of high refractive index nanoparticles, 3 parts of epoxy monomer, 10 parts of acrylic resin, 3 parts of acrylic monomer, 2 parts of photoinitiator, 0.1 parts of surfactant, 45 parts of solvent; wherein:

[0104] The high refractive index nanoparticles are ZrO2 with an average particle size of 22 nm and a refractive index of 2.0;

[0105] The mass ratio of high refractive index nanoparticles to epoxy monomer is 22:3;

[0106] The epoxy monomer is a monomer of formula (5);

[0107] The acrylic resin uses Changxing UV resin ETERCURE 6148J-75;

[0108] The mass ratio of monofunctional (meth)acrylate, difunctional (meth)acrylate and multifunctional (meth)acrylate in the acrylic monomer is 1:3:3;

[0109] The monofunctional (meth)acrylate is ethoxyethoxyethyl acrylate;

[0110] The difunctional (meth)acrylate is tricyclodecane dimethanol diacrylate;

[0111] The multifunctional (meth)acrylate is pentaerythritol tetraacrylate;

[0112] The photoinitiator used was OXE-02;

[0113] The surfactant used is BYK-310 from BYK Chemical;

[0114] The solvent is 3-methoxy-1-butanol.

[0115] Comparative Example 1

[0116] On the basis of Example 1, the difference from Example 1 is that in Comparative Example 1, the epoxy monomer is 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

[0117] Comparative Example 2

[0118] Based on Example 1, the difference from Example 1 is that in Comparative Example 2, 2 parts of high refractive index nanoparticles and 2 parts of epoxy monomers are added, and the mass ratio of high refractive index nanoparticles to epoxy monomers is 1:1, that is, the amount of high refractive index nanoparticles added is too small.

[0119] Comparative Example 3

[0120] Based on Example 1, the difference from Example 1 is that in Comparative Example 3, there are 25 parts of high refractive index nanoparticles and 2 parts of epoxy monomers, and the mass ratio of high refractive index nanoparticles to epoxy monomers is 12.5:1, that is, the amount of high refractive index nanoparticles added is too much.

[0121] Comparative Example 4

[0122] Based on Example 1, the difference from Example 1 is that: in Comparative Example 4, no monofunctional acrylate monomer is added to the acrylic acid monomer.

[0123] Comparative Example 5

[0124] Based on Example 1, the difference from Example 1 is that: in Comparative Example 5, no bifunctional acrylate monomer is added to the acrylic monomer.

[0125] Comparative Example 6

[0126] Based on Example 1, the difference from Example 1 is that: in Comparative Example 5, no multifunctional acrylate monomer is added to the acrylic monomer.

[0127] Comparative Example 7

[0128] Based on Example 1, the difference from Example 1 is that the average particle size of the high refractive index nanoparticles in Comparative Example 6 is ZrO2 of 100 nm.

[0129] Preparation Example

[0130] The preparation process of the negative photoresist with low residual stress and high refractive index provided by the present invention is as follows: adding the above raw materials into a sample bottle according to corresponding weight parts, mixing and stirring evenly, and then obtaining the negative photoresist.

[0131] In addition, the method for preparing a photocurable pattern using the high refractive index negative photoresist is as follows: the obtained high refractive index negative photoresist with low residual stress is spin-coated on a silicon nitride substrate, dried in a vacuum drying oven, and then soft-baked, using a mask with a line / space pattern of 1 to 50 μm, using ultraviolet light with a wavelength of 365 to 405 nm to expose the negative photosensitive resin composition coated on the surface of the glass substrate, and then developing with an aqueous solution of tetramethylammonium hydroxide, washing with deionized water to remove residual developer, and finally baking the developed silicon nitride substrate at 85°C for 60 minutes to obtain a film sample with a thickness of 2 to 3 μm.

[0132] Performance Test:

[0133] (1) Residual stress:

[0134] The film was spin-coated on a 100 μm polyimide substrate. The thickness of the high refractive index OC film after curing was 2 μm. The curvature radius of the film after curing was tested by a laser displacement meter, and the residual stress was calculated using the Stoney formula.

[0135]

[0136] Wherein, Es is the elastic modulus of the substrate (3.2 GPa), Vs is the Poisson's ratio of the substrate (0.37), H is the thickness of the substrate (100 μm), h is the thickness of the film (2 μm), and R is the radius of curvature of the substrate.

[0137] (2) Refractive index:

[0138] A 2cm×2cm×3μm (width×length×thickness) adhesive film is formed on the upper surface of a silicon nitride substrate. The sample is prepared according to the method for forming a solidified pattern, except that a mask is not used. The sample is tested using an ellipsometer, and the refractive index value corresponding to a wavelength of 550nm is selected.

[0139] (3) Light transmittance:

[0140] The samples were prepared according to the method of forming the cured pattern except that no mask was used, and the transmittance of the cured film in the visible light range of 380 nm to 800 nm was measured by an ultraviolet-visible spectrophotometer (U-3900 Hitachi).

[0141] (4) Curing rate:

[0142] A high refractive index negative OC photoresist was inkjet printed on a glass substrate and heated at 30 mW / cm 2The ink was subjected to UV curing for 120 s by UV irradiation to produce a sample with a size of 3 cm × 7.5 cm × 18 μm (width × length × thickness), and then the ink before curing and the organic film after curing were measured using FT-IR (Nicolet iS50, Thermo-Fisher) at 1635 cm -1 (C=C) and 1720cm -1 Absorption peak intensity near (C=O).

[0143] Photocuring rate (%) = |1-(F / S)| × 100;

[0144] Where F is the organic film after curing at 1635cm -1 The absorption peak intensity near 1720cm -1 The ratio of the absorption peak intensities near 1635cm -1 The absorption peak intensity near 1720cm -1 The ratio of the absorption peak intensities near

[0145] (5) Storage stability:

[0146] The flexible high-refractive-index negative OC photoresists obtained in Examples 1 to 5 and Comparative Examples 1 to 7 were stored at 23±2° C. for 120 days, and the viscosity changes were observed;

[0147] <Evaluation Criteria>

[0148] ◎Less than or equal to 1cps;

[0149] ○ Greater than 1cps and less than or equal to 2cps;

[0150] × greater than 2cps;

[0151] (6) Double 85 test conditions:

[0152] At a temperature of 85°C and a relative humidity of 85%, observe the film for 240 hours to see if it falls off or cracks. If no falling off or cracking occurs, it is qualified.

[0153] In order to further verify the effectiveness of the technical solution provided by the present invention, the performance of the photocurable patterns formed by the above-mentioned Examples 1 to 5 and Comparative Examples 1 to 7 was tested, and the results are shown in the following table:

[0154]

[0155] It can be seen from the above table that the photocured patterns corresponding to Examples 1 to 5 have higher transmittance, refractive index and curing rate, and the residual stress is as low as 19.25 MPa. After 240 hours of double 85 aging, there is no obvious change, which effectively reduces the deformation and cracking of the photoresist film, avoids warping and deformation of the product, and ensures that the photoresist pattern has high precision and integrity.

[0156] On the contrary, in Comparative Example 1, the epoxy monomer used was 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane instead of the spirocyclic carbonate compound, and the residual stress was relatively large, and shedding occurred after 72 hours.

[0157] The mass ratio of high refractive index nanoparticles to epoxy monomer in Comparative Examples 2 to 3 is not within the range required by the present invention. In Comparative Example 2, the amount of high refractive index nanoparticles added is too small, and the refractive index is slightly lower than that in Example 1. In Comparative Example 3, the amount of high refractive index nanoparticles added is too large, and the refractive index is higher than that in Example 1. The residual stress is increased compared with Example 1, and different degrees of shedding or cracking occur in the double 85 test, and the storage stability is slightly poor.

[0158] The design of the acrylic monomer in Comparative Examples 4 to 6 is not within the scope required by the present invention, which affects the refractive index. Compared with Example 1, the refractive index is slightly increased, and the film may crack or fall off in the double 85 test. In Comparative Example 7, the high refractive index nanoparticles are selected from ZrO2 with a larger average particle size. Compared with Example 1, the overall performance of the corresponding photocurable pattern is poor.

[0159] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention.

[0160] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.

Claims

1. A high refractive index negative OC photoresist with low residual stress, characterized in that: The raw materials are as follows, measured by weight: 10 to 22 parts of high refractive index nanoparticles, 2 to 3 parts of epoxy monomers, 3 to 10 parts of acrylic resins, 1 to 3 parts of acrylic monomers, 1.5 to 4 parts of photoinitiators, 0 to 4 parts of photosensitizers, 0.01 to 0.5 parts of surfactants, 0 to 2 parts of curing agents, and 30 to 70 parts of solvents.

2. The high refractive index negative OC photoresist with low residual stress according to claim 1, characterized in that: The epoxy monomer is selected from spirocyclic orthocarbonate compounds, and the structural formula is one of the following structural formulas:

3. The high refractive index negative OC photoresist with low residual stress according to claim 1, characterized in that: The acrylic resin is a UV-curable acrylic oligomer.

4. The high refractive index negative OC photoresist with low residual stress according to claim 1, characterized in that: The acrylic monomer is a mixture of one or more of the following: monofunctional (meth)acrylate of C1 to C30 monohydric alcohol or polyhydric alcohol, difunctional (meth)acrylate of C2 to C30 monohydric alcohol or polyhydric alcohol, and multifunctional (meth)acrylate of C3 to C30 monohydric alcohol or polyhydric alcohol.

5. The high refractive index negative OC photoresist with low residual stress according to claim 1, characterized in that: The photoinitiator includes an oxime ester photoinitiator and a cationic photoinitiator; the oxime ester photoinitiator includes one or more of OXE-01, OXE-02, OXE-E12, and OXPI-405; the cationic photoinitiator includes one or more of diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate, bis(4-tert-butylphenyl)iodonium hexafluorophosphate, triphenyl hexafluorophosphate sulfonium salt, and triphenyltetrakis(pentafluorophenyl)borate sulfonium salt.

6. The high refractive index negative OC photoresist with low residual stress according to claim 1, characterized in that: The photosensitizer includes one or more of 2-isopropylthioxanthone, 9,10-dibutoxyanthracene, benzoin dimethyl ether, 1-hydroxycyclohexyl phenyl ketone, 1-chloro-4-propoxythioxanthone, and ethyl p-N,N-dimethylaminobenzoate.

7. The high refractive index negative OC photoresist with low residual stress according to claim 1, characterized in that: The curing agent includes one or more of methyltetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylnadic anhydride, acetic anhydride, propionic anhydride, benzyldimethylamine, N,N-dimethylcyclohexylamine, bis(2-dimethylaminoethyl) ether, N,N,N',N'-tetramethylalkylenediamine, and triethylamine.

8. A method for preparing a photocured pattern formed by a high refractive index negative OC photoresist with low residual stress, characterized in that: The steps include: 1) firstly coating the negative OC photoresist with low residual stress and high refractive index as claimed in any one of claims 1 to 7 on a substrate; 2) heating and drying the film to remove volatile components to obtain a smooth film; wherein the heating temperature is 70 to 90° C., and the thickness of the film after heating is 2 to 8 μm; 3) Finally, the obtained film is irradiated with ultraviolet light through a mask, so that the film cured by ultraviolet light is brought into contact with a developer to dissolve the unexposed area for development; after the development is completed, the pattern is washed with water, blown dry with nitrogen, and then post-baked at a temperature of 70 to 100° C. for 10 to 100 minutes to complete the preparation of the photocured pattern.

9. An application of a photocurable pattern formed by a high refractive index negative OC photoresist with low residual stress, characterized in that: The photocurable pattern is prepared by the preparation method according to claim 8 and is applied to a microlens array, an array flattening film pattern, a protective film pattern or an insulating film pattern.

10. An image display device, characterized in that: The image display device comprises a photocurable pattern obtained by the preparation method according to claim 8; the image display device comprises a liquid crystal display device, an organic light emitting diode or a flexible display.

Citation Information

Cited By

  • Preparation method and application of undercut-free high-refractive-index negative OC photoresist and photocuring pattern

    CN119846903A

  • A high refractive index negative OC photoresist without undercuts, a method for preparing and applying a photocured pattern

    CN119846903B

  • Low-shrinkage and low-vacuum-deflation transparent composition photoresist and preparation method for preparing cured coating by using low-shrinkage and low-vacuum-deflation transparent composition photoresist

    CN120949511A